Pengaruh Implementasi Media Pembelajaran Tas Ajaib Dalam Upaya Mengenal Identitas Diri Dan Keluarga Pada Siswa Kelas 1 SD Islam Al-Mubarok Surabaya - Al Fatich, Vahid Najich; Alamsyah, Artika Devi; Taqiardi, Khanza Hisyambara; Staniyah, Adduha Walidatus; Hendira, Galuh Shafwah Putri; Ramadhani, Tutitya Qodrianisa; Istiq'faroh, Nurul; Zahroh, Ulfi Aminatuz (Journal of Contemporary Issues in Primary Education, 2024)
The present study aims to promote self-knowledge and familial awareness among children, thereby facilitating their socialization. The objective is threefold: first, to enhance students' interest and motivation in the learning process; second, to assist them in recognizing their own selves; third, to encourage interaction and collaboration among students; and fourth, to provide a learning experience that is both educational and enjoyable. Conventional learning media is often regarded as less appealing to early childhood students. This study proposes the utilization of "Magic Bag" media as an interactive and innovative alternative. The "Magic Bag of Self and Family Identity" media is hypothesized to facilitate the implementation of the self-introduction process for grade 1 students at Al-Mubarok Islamic Elementary School in an effective, engaging, and memorable manner, thereby fostering the development of crucial social and emotional competencies. The findings of the research are as follows: Firstly, the development of the conventional-based "Magic Bag" learning media on self-identity and family material is systematic and structured in accordance with the stages of the development research model. Secondly, the conventional-based "Magic Bag" learning media is declared very valid with an average percentage level The material validation percentage was found to be 90.76%, while the media validation percentage was 92.30%. Furthermore, the "Magic Bag" learning media has been determined to be highly effective, with a student learning completeness percentage of 98.33% in a limited trial.